Jedność nauki wczoraj i dziś - Strawiński, Witold (Filozofia Nauki, 1996)
The author deals with the problem of the unity of science. Four main ideas of logical empiricism connected with the unity of science: unity of language, unity of laws, unity of methods and the unity of scientific practice are considered from contemporary point of view.